PT Bali Hai Cruises Nusantara’s corporate social responsibility activities in Nusa Lembongan Bali - I Nyoman Mokoh Wijaya; I Ketut Sutama (Politeknik Negeri Bali, 2020)
Purpose: This research was conducted to know the forms of corporate social responsibility (CSR) program, the disclosure of corporate social responsibility, and the implementation of corporate social responsibility on stakeholders.Research methods: The data used in this research was secondary data. This research was conducted in a qualitative method in which the data collections were through observation and documentation.Results and discussion: The results showed that the implementation of the international conventions cluster showed that the companies implemented the role and regulation of sustainable tourism in using the land and the environmentally friendly materials for building. The result also implemented the National law and regulations cluster which are concerned about employee health and safety as it is considered that the activities do mostly in the sea. Meanwhile, the local decreases cluster showed that CSR's program implemented three different aspects of sustainable tourism. These aspects are economic, ecology and social culture.Conclusion: Overall PT Bali Hai Cruises Nusantara implemented the CSR program to local stakeholders in order to keep the company's sustainability.